Association between depressive symptoms and psychosocial factors and perception of maternal self-efficacy in teenage mothers - Lara, María Asunción; Patiño, Pamela; Navarrete, Laura; Hernández, Zaira; Nieto, Lourdes (2017)
ABSTRACT Introduction. Teenage pregnancy is a national health priority. Having to deal with pregnancy during adolescence can cause the mother, at an already vulnerable age, to doubt her maternal capacity to cope with a challenge of this magnitude. The teenage mother’s assessment of her maternal self-efficacy is associated with her performance, in other words, the way she relates and responds to the needs of her infant, which has major implications for the latter’s development. Objective. To study the association between personal (depressive symptoms, self-esteem) and environmental characteristics (social support, partner satisfaction) and those of the infant (problems with infant care, the infants’s temperament) and the perception of maternal self-efficacy (PME) in adolescent mothers. Method. Cross-sectional study. The following instruments were applied: Center for Epidemiologic Studies Depression Scale (CES-D), Post-partum Depression Predictors Inventory-Revised (PDPI-R), and Maternal Efficacy Questionnaire to 120 mothers under 20 during the first six months postpartum. Bivariate lineal regression and hierarchical linear regression analyses were used for the data analysis. Results. When adjusting for other variables, symptoms of depression and difficult infant temperament were associated with lower PME. Social support was only associated with increased PME in the bivariate analysis. Discussion and conclusion. These findings contribute to the limited literature on the subject and provide elements for designing strategies to improve adolescent mothers’ PME to encourage behaviors that are more relevant and sensitive to infants’ physical and emotional needs. Keywords: Postpartum depression, maternal self-efficacy, adolescents, psychosocial factors.